REGULASI RETRIBUSI, FASILITAS PELAYANAN PASAR, TARIF RETRIBUSI DAN KEMAUAN MEMBAYAR RETRIBUSI PASAR - Fatmala, Wilda; Husriah, Husriah; Farida, Eka Yuni (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
Mawasangka Market experienced a significant decline in levy revenue in 2021, worsening in 2022, when it ceased to be the market with the highest levy revenue, experiencing a decline of up to 78.77%. This study explores the influence of Levy Regulation, Market Service Facilities, and Levy Rates on the Willingness to Pay Market Levies. The research population consists of all traders in Mawasangka Market, totaling 300, in Buton Tengah Regency. The sample size, determined through simple random sampling techniques, comprises 75 traders. The analysis of variable relationships was conducted through instrument requirement tests, data analysis requirement tests, t-tests, and f-tests using the SPSS software. The research findings indicate that Levy Regulation and Market Service Facilities do not affect traders' willingness to pay Market Levies, while Levy Rates have an influence on this willingness. Simultaneously, these factors collectively impact traders' willingness to pay at the market. Based on the research results, there is a need to review policies related to levy regulation, market facilities, levy rates, and other factors to enhance revenue collection through market levies and improve overall market conditions. Keywords: Market Service Facilities, Willingness to Pay, Levy Regulation, Levy Rate